ASSESSMENT OF FACTORS IN THE PERFORMANCE OF THE MANUFACTURING INDUSTRY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Any success or failure of the manufacturing industry, according to scientists, indicates the processes that are going to occur in the entire national economy in the future as well as the overall current state of the national economy. In Latvia, small and medium enterprises engaged in the manufacturing industry make up the largest proportion of market sector economically active statistical units, and the value added generated by small and medium manufacturing enterprises represents the largest proportion of total value added generated by the manufacturing industry. The research aims to identify and assess factors in the performance and development of the manufacturing industry and small and medium manufacturing enterprises in Latvia. The research employed general scientific research methods: monographic, descriptive and graphic as well as analysis and synthesis. The Cobb-Douglas model was used to assess the situation in the manufacturing industry and identify the effects of factors on economic growth. The research identified and assessed the factors in the performance and development of the manufacturing industry and small and medium manufacturing enterprises in Latvia.